RANCANG BANGUN SISTEM INFORMASI PENYIMPANAN DATA HISTORIS PENGGUNAAN ALAT UKUR BERBASIS WEBSITE MENGGUNAKAN MODEL WATERFALL DI LABORATORIUM TRANSMISI TELKOM TEST HOUSE - Galih Galih; Angelarah Natalia; Fahmi Naufal Ridwan (STKIP PGRI Situbondo, 2023)
This research aims to design and build a website-based information system for storing historical data on the use of measuring instruments in the Telkom Test House PT Telkom Indonesia transmission laboratory using the waterfall model. This system will make it easier for users to access and store data on the use of measuring instruments. The data collection method was carried out through observation and interviews with transmission laboratory personnel at the Telkom Test House. Furthermore, data analysis is carried out to design and build the right system according to user needs. This information system was built using the PHP programming language with a MySQL database and designed to be easy to use and access through the website. The result of this research is a website-based information system that can be used to store historical data on the use of measuring instruments in the Telkom Test House transmission laboratory with features that make it easy for users such as login, account registration, and searching and processing data on the use of measuring instruments. It is hoped that this information system can help the Telkom Test House transmission laboratory in facilitating the process of managing historical data on the use of measuring instruments.